Kemitraan Substantif SMK-DUDI dalam Manajemen Pendidikan Kejuruan: Kajian Literatur Sistematis - Muhammad Satrio Utomo; Fannia Rahadatul Aisy; Nurmila Pra Astuti; Andika Santoso (Sahabat Akademia Group, 2026)
This article examines substantive partnerships between Vocational High Schools (SMKs) and the Business and Industrial Sectors (DUDI) within vocational education management. Using a Systematic Literature Review guided by PRISMA 2020, this study synthesizes four empirical articles indexed in SINTA 1–3 and published between 2021 and 2026. The thematic synthesis identifies school-industry partnership management, curriculum alignment, graduate competence development through industrial work practice, and the role of school public relations in sustaining collaboration. Findings indicate that effective partnerships require structured planning, organizing, implementation, and evaluation, supported by active industry involvement in curriculum synchronization, teaching factory programs, internships, and competency assessment. However, many partnerships remain administrative due to limited industrial partners, schedule mismatches, weak evaluation indicators, and differing school-industry orientations. The study recommends sustainable link and match strategies to strengthen graduate competence, learning quality, and institutional accountability.